Optimalisasi Informasi Manajemen Laporan Assignment Pada Website Berbasis Content Management System - Rahardja, Untung; Aini, Qurotul; Apriani, Desy; Khoirunisa, Alfiah (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
As we know today, Indonesia has entered the era of revolution 4.0 which in that era had a significant influence on the changes that took place in all fields. Including in the area of education, in particular, the changes that occur in the world of education today are so rapid with the abandonment of learning methods that still use conventional methods. Doing tasks with books, face-to-face communication, collecting assignments in hard copy, which will undoubtedly cause a lot of losses in a certain period, such as many assignments that are long buried and difficult to find when needed. This method is undoubtedly considered an annoying and time-consuming way, where students cannot explore in the learning process which will take a long time to do a manual search for the number of files that have been collected. At present, the application of learning methods with concepts organizes many reports on the work of assignments on a website content management system. This learning method is made to maximize the way to hold student assignment reports for time management efficiency. Therefore this learning method can be applied as the management of education in higher education. It is expected that the existence of this method can improve time management in learning so that it motivates to explore abilities in the existing learning process. Keywords: Manajemen, Content Manajemen System, Assignment